Profile of Flexibility and Arm Muscle Power of Palembang City FPTI Athletes - Vitara Vitara; Bayu Hardiyono; Selvi Atesya Kesumawati; Muslimin Muslimin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research aims to determine the physical profile of Palembang City FPTI athletes. The physical profile measured includes Flexibility and Arm Muscle Power. This research is quantitative descriptive. The method used in this research is a survey method with data collection techniques in the form of tests and measurements. The population in the study were 18 FPTI athletes from Palembang City. The test and measurement indicators were the Flexibility test (sit and reach test) and the Muscle Power test (Pull Dynamometer). The selection of research subjects used total sampling, obtaining the entire population as subjects. The data analysis technique is descriptive. The results of research on physical condition profiles using tests and measurements show the following results: (1) Flexibility of FPTI athletes in Palembang city is categorized as "very good" with a percentage of 100%, (2) Arm muscle strength of FPTI athletes in Palembang city shows that two athletes (11 %) got a very good score, five athletes (27%) got a good score, and five athletes (27%) got a poor score. Apart from that, four athletes (22%) received the very poor category.